2014
DOI: 10.1007/82_2014_368
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Outbreaks in India

Abstract: Cholera is a global health problem as several thousands of cases and deaths occur each year. The unique epidemiologic attribute of the disease is its propensity to occur as outbreaks that may flare-up into epidemics, if not controlled. The causative bacterial pathogen Vibrio cholerae prevails in the environment and infects humans whenever there is a breakdown in the public health component. The Indian subcontinent is vulnerable to this disease due its vast coastlines with areas of poor sanitation, unsafe drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 116 publications
0
21
0
1
Order By: Relevance
“…Sanitation facilities, provision of safe drinking water and good infrastructure for sewage treatment in industrialized nations has made cholera extremely rare. Outbreak studies done in Odisha, India found a clear relationship between sewage contaminated water and cholera epidemics [48]. Several field surveys in West Bengal and Gujrat revealed cholera outbreaks related to sewage leaks from municipality pipelines and local overpopulation [4951].…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…Sanitation facilities, provision of safe drinking water and good infrastructure for sewage treatment in industrialized nations has made cholera extremely rare. Outbreak studies done in Odisha, India found a clear relationship between sewage contaminated water and cholera epidemics [48]. Several field surveys in West Bengal and Gujrat revealed cholera outbreaks related to sewage leaks from municipality pipelines and local overpopulation [4951].…”
Section: Other Environmental Factorsmentioning
confidence: 99%
“…2,3 In addition, one or the other part of the country continues to endure outbreaks of this illness every year, especially during monsoon seasons. 4 Though, it is the fluid and electrolyte replacement that plays a critical role in management of cholera, antibiotic intervention may be warranted, particularly in severe cases. For the patient, it is beneficial since it reduces the intensity and duration of diarrheal disease and prevents any lethal complications.…”
Section: Introductionmentioning
confidence: 99%
“…The isolates from U.K. travelers clustered geographically with those returning from India located on the same branch, and those reporting recent travel to Pakistan clustered on a separate branch. Further analysis based on single nucleotide polymorphisms in the core genome compared with a reference strain may be performed for outbreak detection and source attribution where the incidence of the current V. cholerae O1 El Tor pandemic lineage (ST69) is high (28,29).…”
Section: Resultsmentioning
confidence: 99%